Post-larval stages of Ascoschoengastia (Laurentella) lorius (Gunther) (Acariformes: Trombiculidae) provide evidence for a nest-based life history - Shaw, Matthew (Zootaxa, 2010)
While certain ecological groups of trombiculid mites are thought to be specialised for nest occupation, supporting evidence is rare. A putatively nest-specialised trombiculid is here described in detail. Larvae, a deutonymph and adults of the trombiculid genus Ascoschoengastia were collected from three tree hollow nests occupied by Eclectus parrots (Eclectus roratus) and Sulphur-crested Cockatoos (Cacatua galerita) at Iron Range, Cape York Peninsula. The larvae are A. (Laurentella) lorius (Gunther), a species originally described from an Eclectus parrot in Papua New Guinea. Deutonymph and adult Ascoschoengastia are also assigned to this species based on their co-occurrence with larvae in this specific and isolated microhabitat. A. (L.) lorius is inferred to have a nest-based life history. Active stases are described with attention to sensory setae. The previous synonomy of A. (L.) daria with A. (L.) lorius is rejected. A key to Australian species of Ascoschoengastia is presented.